Nonlinear control of autonomous underwater vehicle in shallow water environment - Liu, Shu Yong (2010)
This dissertation presents new results on the design of output feedback control systems for Autonomous Underwater Vehicles (AUVs) operating in very shallow water/surface zone (V8W/8Z) areas. The V8W and 8Z areas are defined as water depths of 40 feet to 10 feet and 10 feet to water surface, respectively.